Death of a gigolo - Levine, Laura, 1943- (Levine, Laura, 1943- Jaine Austen mystery., 2019)
Daisy Kincaid is in her sixties and heiress to a fortune. Now she wants to make a name for herself as a romance author . . . with a little help from Jaine, that is. As Jaine labors away on love scenes, she gets to know the wealthy woman<U+2019>s gentleman friend, her household staff, and her social circle<U+2014>every one of whom is horrified when Daisy falls under the spell of a much younger stud named Tommy, a rude, crude lothario who<U+2019>s made himself a fixture in Daisy<U+2019>s Bel Air mansion. After Tommy and Daisy shock everyone by announcing their engagement, it doesn<U+2019>t take long for someone to stab him in the neck<U+2014>with the solid gold Swiss Army knife that Daisy gave him as a gift. The challenging part is trying to narrow down the list of suspects. Jaine<U+2019>s going to have to put a bookmark in that love story and focus all her creative talent into untangling a tale of money and murder . . .